Breast augmentation: correlation between surgical planning and complication rates after surgery - João Maximiliano; Antonio Carlos Pinto Oliveira; Emilaine Lorencetti; João Bombardelli; Ciro Paz Portinho; Daniel Deggerone; Jorge Hoyos; Marcus Vinicius Martins Collares (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Breast implants remain a very popular option both for aesthetic and reconstructive plastic surgeries. A number of factors can affect the results of breast implant surgeries. The adequate planning on incision placement, need to associate mastopexy, insertion plane, and implant model increase the likelihood of adequate outcomes and reduce the need for secondary surgical treatment. This study describes the experience of a Plastic Surgery Service at the Hospital de Clínicas de Porto Alegre from 2011 to 2016 by correlating surgical planning with complication rates and surgical reintervention. METHODS: A retrospective cohort that analyzed patients who underwent breast implants at the Hospital de Clínicas de Porto Alegre between 2011 and 2016, and included only cases of aesthetic breast augmentation, associated or not with mastopexy. All patients had their records analyzed, and after that an interview by phone was conducted to complement the information of the questionnaire. The analyzed was concluded with an appointment with a plastic surgeon of the service who examined the patient and confirmed the data collected for the questionnaire. No patients was evaluated by the assistant surgeon in last examination. RESULTS: There was no significant difference between variation in surgical planning and incidence of complications. CONCLUSION: Still, no consensus exists regarding the best access route and plan for the breast implant. Further studies are necessary to compare the different routines of each service. Currently, best results are still based on routine systematization, precise surgical dissection and minimal contamination.